Efficacy of synbiotic supplementation in improving rheumatoid arthritis - Farah Esmaeili; Mansour Salesi; Gholamreza Askari; Ali Esmaeilisharif; Mohammadreza Maracy; Hadi karimzadeh; Behrokh Shojaie (Wolters Kluwer Medknow Publications, 2020)
Background and purpose: Today, improving rheumatoid arthritis (RA) as a chronic inflammatory disease is attributed to the proper status of the gut microbiota. Although some supplements containing beneficial live microorganisms (probiotics) can reduce inflammation by altering the bacterial composition of the gut, there is limited information on the effect of synbiotic (probiotics mixed with prebiotics) supplements on RA. Therefore, this study aimed to evaluate the anti-inflammatory effects of a synbiotic supplement as an adjuvant therapy in rheumatic patients. Moreover, for the first time, it was attempted to investigate whether addition of a synbiotic (1000 mg/day) to the combination of methotrexate and prednisolone increases the effectiveness of these antirheumatic drugs. Experimental approach: Eligible patients (186 subjects) were randomly divided into two groups. Both groups received their standard routine antirheumatic drugs, methotrexate and prednisolone. Moreover, the first group received a daily oral synbiotic supplement (1000 mg) for 3 months while the second group received a placebo. Various parameters indicating RA status were evaluated at baseline (time 0) and 3 months after the treatment. Findings / Results: The results showed the changes in the level of RA indicators, including tender joint count with a range of 0 to 28 joints, swollen joint count with a range of 0 to 28 joints, visual analog scale, erythrocyte sedimentation rate, CRP, and disease activity score based on 28 joints, after 3 months Conclusion and implications: Overall, no significant differences in the measured parameters were observed between synbiotic and placebo groups probably due to the short duration of the treatment period, and it is suggested to extend the treatment period to six months.